Desarrollo de prácticas de dinámica de fluidos computacional (CFD) como complemento didáctico del laboratorio de energía y fluidos de la CIEM-UNL. - Jiménez Cueva, Bryan Santiago (2021)
The present graduation project is about a testing platform concerning of numeric simulation, destined to the Electromechanical Engineering career. This platform is precisely for the study of Computational Fluid Dynamics (CFD) and it is related to the next professional university subjects: Fluid Mechanics (five practices), Heat Transfer (two practices), Fluid Machines (two practices), and Renewable Energies (one practice). These practices allow improving the learning methodology in students, where the theory is not enough and the practical part is necessary to consolidate the knowledge given by teachers. Firstly, all the professional subjects into the Electromechanical Engineering career (regime 2013) related to CFD were analyzed, where possible topics of practice with numeric simulation could have been made. After this, there was a discussion with all the teachers from the October 2019-March 2020 period and the leading person of the project. Then a Testing Platform was proposed. Once the idea was chosen, a bunch of bibliographic information about CFD was collected as well from scientific magazines and previous works such like: Ayuso (2014), Garrido (2017), Gonzáles (2000), Cortés, Fazio, Rao, Bustamante, & Vera (2014), Cedillo & Marín (2005), Herrera & Puerto (2016) y Kaiser & Zamora (2009). After this, a specific methodology was made for the preparing parameters for simulation, which is expressed in modelo de guía digital section. Multimedia guides for each numeric simulation were also made, and indicate the configurations carried out in the ANSYS® Student 2020 R2 software. Finally, each simulation practice was validated by comparing the results presented in books, previous projects, scientific articles, and experimentations; with those obtained through numerical simulations, finding equivalent or equal results for all the study cases. Key words: didactic guides, computational fluid dynamics, numerical simulations.